A BEME systematic review of the effects of interprofessional education: BEME Guide No. 39. (2nd July 2016) - Reeves, Scott; Fletcher, Simon; Barr, Hugh; Birch, Ivan; Boet, Sylvain; Davies, Nigel; McFadyen, Angus; Rivera, Josette; Kitto, Simon
Abstract: Background: Interprofessional education (IPE) aims to bring together different professionals to learn with, from, and about one another in order to collaborate more effectively in the delivery of safe, high-quality care for patients/clients. Given its potential for improving collaboration and care delivery, there have been repeated calls for the wider-scale implementation of IPE across education and clinical settings. Increasingly, a range of IPE initiatives are being implemented and evaluated which are adding to the growth of evidence for this form of education. Aim: The overall aim of this review is to update a previous BEME review published in 2007. In doing so, this update sought to synthesize the evolving nature of the IPE evidence. Methods: Medline, CINAHL, BEI, and ASSIA were searched from May 2005 to June 2014. Also, journal hand searches were undertaken. All potential abstracts and papers were screened by pairs of reviewers to determine inclusion. All included papers were assessed for methodological quality and those deemed as "high quality" were included. The presage–process–product (3P) model and a modified Kirkpatrick model were employed to analyze and synthesize the included studies. Results: Twenty-five new IPE studies were included in this update. These studies were added to the 21 studies from the previous review to form a complete data set of 46 high-quality IPE studies. In relation to the 3P model, overall the updated review found that most of the presage and process factors identified from the previous review were further supported in the newer studies. In regard to the products (outcomes) reported, the results from this review continue to show far more positive than neutral or mixed outcomes reported in the included studies. Based on the modified Kirkpatrick model, the included studies suggest that learners respond well to IPE, their attitudes and perceptions of one another improve, and they report increases in collaborative knowledge and skills. There is more limited, but growing, evidence related to changes in behavior, organizational practice, and benefits to patients/clients. Conclusions: This updated review found that key context (presage) and process factors reported in the previous review continue to have resonance on the delivery of IPE. In addition, the newer studies have provided further evidence for the effects on IPE related to a number of different outcomes. Based on these conclusions, a series of key implications for the development of IPE are offered.